Improving the Understanding of Fiqh Lessson through Studying the Fathul Qorib - Muhammad Fodhil; Ahmad chaerurriziq (SCHOOLAR: Social and Literature Study in Education, 2022)
Pondok Pesantren is a place where the learning system uses the yellow book, there are many books that are studied in the pesantren, one of which is the book of fathul qorib, the start of learning fiqh using the book of fathul qorib in Madrasah Diniyah Islamic Boarding School Salafiyah Syafi'iyah Seblak Jombang In 1921, which is when the establishment of this Islamic boarding school was started, so that studying the book of fathul qorib has become an obligation that must be developed to date, as is the method of delivery, namely to improve. Learning fiqh material so that students are able to understand, translate, interpret and solve problems in the book fathul qorib. This article is a case study with a qualitative approach, the results of this study are to improve understanding of fiqh material through the study of the fathul qorib book at Madrasah Diniyah Islamic Boarding School Salafiyah Syafi'iyah Seblak Jombang. In the process of increasing students' understanding, namely by using the sorogan, bandongan, practice, discussion and lecture methods. So this learning method aims so that students can read, translate and explain fiqh material through book study fathul qorib by using their own language, the teacher also strengthens the understanding of students in the science of nahwu and shorof so that students can read books fathul qorib without any sense and meaning.